The use of online disputes resolution mechanisms in the settlement of commercial disputes in Nigeria: challenges and prospects (2018)
Commercial transactions have gone beyond traditional face-to-face level to online. Today, the distance between a seller and a prospective buyer of goods and services is only a click away as the internet has transformed the world to a global village. The evidence of this is seen in the emergence of online supermarkets such as jumia, konga, amazon, ebay, yudala, jiji, OLX, etc. which offer various products and services. It is needless to emphasize that in the course of transacting business whether online or offline, dispute may arise, hence, the need for disputes resolution. Traditionally, litigation have served as the main dispute resolution platform but due to certain inadequacies such as technicality and formality, there have been a move to Alternative Dispute Resolution (ADR) which is reputed as being informal, confidential, relatively cheap, speedier, etc. However, in settling disputes, providers and users of ADR have moved from offline ADR to online ADR (ODR) which is the use of online ADR Mechanisms in the online environment mainly precipitated by e-commerce. These ODRs mechanisms include online mediation, arbitration and negotiation through technological devices such as e-mails, e-signature, video-conferencing and chats. This article examines the meaning of ADR and ODR by accentuating the differences between them. It also discusses the types of ODR mechanisms, the legal framework of traditional ADR and ODR in Nigeria. The article further highlights the challenges confronting the utilization of ODR in Nigeria and ways to overcome them as well as the prospects of ODR in Nigeria. It makes some recommendations especially the need for the amendment of the Arbitration and Conciliation Act to give ODR statutory backing before concluding.